CAG Research Committee Report: Another Stellar Year for Canadian GI Research - Derek M McKay (Canadian Journal of Gastroenterology)
The goal of the Research Committee is to build, in collaboration with the Canadian Institutes of Health Research (CIHR) and the Canadian Association of Gastroenterology (CAG) partners, Canadian capacity and expertise in the discipline of gastroenterology and nutrition, and to promote excellence in research. As chair of the CAG Research Committee, it is my privilege to update the CAG membership and The Canadian Journal of Gastroenterology readership on the activities of the CAG Research Committee (2003-2004), in what has been yet another outstanding year for investment in gastrointestinal (GI) research in Canada.